DIVERSITY AND WHITE SUPREMACY CONCEPT IN THE ADAPTATION OF BARBIE: FROM A DOLL INTO A VIDEO BLOG - R Hariyani Susanti (British : Jurnal Bahasa dan Sastra Inggris, 2021)
AbstractBarbie doll for some people is only childhood plaything that holds memories, but for some others, it is a representation of one race that neglects the others. However, this problem was addressed in 2016 which when Mattel produced diverse dolls that represent people of other races, body types, skin colors, and many more.  Yet there is still one platform that they have not change, that is when they adapted into YouTube, the video blog or vlog concept of Barbie. These two mediums both are created by one giant company that should value the same ideology. This study is conducted using comparative study to analyze both medium and applied diversity theory by Parekh to find out the diversity concept valued by Mattel. The findings show how Mattel still uphold some white supremacies ideology in its lack of diversity in the video blog production.Keywords: Diversity, White supremacy, Adaptation